The Effect of Brand Image and Ease of Use on the Decision to Purchase Bus Tickets Online at the Cengkareng Suspension Bridge Agent, West Jakarta - Wahyuddin Latunreng; fita rahmawaty (Majalah Ilmiah Bijak, 2021)
The purpose of this study was to determine the effect of compensation and motivation on employee performance with job satisfaction as an intervening variable at Hotel XYZ Jakarta. This study uses a quantitative approach, associative research type and the sample in this study amounted to 120 people, using primary data obtained from a questionnaire with the Simple Random Probability sampling method. Data collection using the questionnaire method, hypothesis testing includes path analysis, MSI transformation, single test, direct effect, indirect effect, path coefficient and determination coefficient (R2). The results showed that motivation and compensation had a positive and significant effect on job satisfaction and employee performance. Job satisfaction also has a positive and significant effect on employee performance. Simultaneously compensation, motivation affects job satisfaction and motivation, compensation, and job satisfaction affect employee performance. The results of the analysis show that the direct path of motivation has the strongest influence on employee performance as indicated by the regression coefficient of the highest (dominant) influence of 0.448.Â